Relationship Between Mothers’s Nutritional Knowledge and the Nutritional Status of Stunted Toddlers in Nyawangan Village, Sendang Health Center, Tulungagung Regency - Meisya Argia Sisviani Deva DEVA; Nuning Marina Pengge; Mujayanto (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Stunting remains a chronic nutritional problem affecting children's physical growth, cognitive development, and future productivity. This study aims to examine the relationship between maternal nutritional knowledge and the nutritional status of stunted toddlers in Nyawangan Village, Tulungagung Regency. This research employed an observational analytic method with a retrospective approach. A total of 58 mothers of toddlers were selected using simple random sampling, and data were collected via questionnaires. The results showed that 51.7% of mothers had poor nutritional knowledge and 55.2% of toddlers were stunted. Spearman’s test indicated a weak positive correlation between maternal knowledge and children's nutritional status, but the result was not statistically significant (r = 0.165; p = 0.216). Although not significant, the findings suggest that better maternal knowledge tends to be associated with better nutritional status in children. Therefore, nutrition education for mothers should be enhanced by considering other contributing factors such as economic status, environment, and parenting practices.